INTEGRASI MAKNA AGAMA DAN SOSIAL DALAM TRADISI TUDUNG LINGKUP BUDAYA MELAYU JAMBI PADA SISWA SEKOLAH DASAR - Apriyani Br Tambunan; Rayi Arista Mukti; M. Riski Saputra; Della Enjelina; Putri Dwi Rosadi; Puspitri Mayang Sari; Debora Angelina Simarmata; Silvi Angeliani; Denada Viqri; Arini Syafitri; Mawaddah; M. Fattur Rozi; Mulyani Br Situmorang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ocal culture has an important role in shaping community identity and as a means of character education, as reflected in the Tudung Lingkup Tradition in Jambi. This tradition combines religious and social values, showing a symbol of Jambi Malay cultural identity as well as obedience to Islamic teachings. Tudung Lingkup, as part of women's traditional clothing, is used to cover the aurat according to Islamic law, as commanded in the Qur'an. This symbol represents the value of purity, honor, and harmony between custom and religion. In addition, the Tudung Lingkup Tradition teaches social values such as togetherness and solidarity, which are relevant for student character building in elementary schools. This research uses a descriptive method with a qualitative approach to comprehensively describe the Tudung Lingkup Tradition. Data collection was done through interviews with traditional leaders, direct observation, and literature study. The results showed that this tradition has existed since before the 1960s and is practiced by women in the Seberang area of Jambi City. The wearing of tudung lingkup, which covers head to toe except the face, reflects a woman's age and marital status and protects them from slander. The Tudung Lingkup tradition has great potential to be integrated in basic education. Through thematic learning and hands-on practice, students can understand cultural and religious values, while instilling a love for local traditions. This effort is important in facing the challenges of globalization that tend to erode local values. By introducing the Tudung Lingkup Tradition in the educational environment, the younger generation is expected to not only preserve cultural heritage, but also build ethical character in accordance with religious and national values.